The advantages of mobile applications in teaching chemistry in distance learning - Khidirbayeva Dilarom; Abisheva Aigul Kadyrbekovna (Progress in Science, 2023)
The relevance of this article lies in the practical study of the problem of using mobile applications in the modern educational process and the description of the forms and methods for introducing mobile Internet devices into the educational process.